The blacklist. The complete second season [videorecording (DVD)]. - Spader, James; Boone, Megan, 1983-; Klattenhoff, Diego (Sony Pictures Home Entertainment, 2015)
On Liz Keen's first day, Raymond Reddington walks into the FBI insisting to talk to her. Reddington is also on the FBI's Top Ten Most Wanted list.